2021
DOI: 10.1002/jper.20-0772
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction reduces hepatic alterations associated with experimental periodontitis

Abstract: Background: Periodontitis is a chronic inflammatory and multifactorial disease that affects the periodontal structures and can cause alterations in the hepatic tissue. The aim of the present study was to evaluate whether a diet with food restriction can decrease oral and liver alterations associated with ligature-induced periodontitis.Methods: Twenty-four female Wistar rats were used in this study, randomized into three groups (n = 8 for each group): control (regular food); periodontitis (regular food + period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The activation of caspase family proteins is an important sign of apoptosis. Therefore, an activity assay was used to detect the effect of DhHP-6 on HGFs [ 29 ]. As shown in Figure 1 D, the activity levels of caspase-3, caspase-8, and caspase-9 in cells treated with DhHP-6 + H 2 O 2 were significantly lower than those in cells treated with H 2 O 2 alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of caspase family proteins is an important sign of apoptosis. Therefore, an activity assay was used to detect the effect of DhHP-6 on HGFs [ 29 ]. As shown in Figure 1 D, the activity levels of caspase-3, caspase-8, and caspase-9 in cells treated with DhHP-6 + H 2 O 2 were significantly lower than those in cells treated with H 2 O 2 alone.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that DhHP-6 has anti-inflammatory effects as a peroxidase-mimicking enzyme. Our results indicated that DhHP-6 has therapeutic effects in periodontitis by reducing the levels of the inflammatory factors TNF-α and IL-1β in HGFs sensitized by LPS and reducing the cellular inflammatory response [ 29 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…[88] One study found that food restriction in rats reduced oral damage as well as alveolar bone changes hepatic, blood, and associated with ligature-induced periodontitis. [89] In a ligature-induced periodontitis model study, bromelain was administrated to rats. It was shown that bromelain improved the steatosis scores.…”
Section: Periodontal Problems and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Recent studies have shown an association between NAFLD and CP 10 . On the other hand, some observational and experimental studies have suggested a potential link between CP and NAFLD 11,12 . However, the previously published studies have limitations in evaluating the causal effects, which require controlling the biases and confounding factors.…”
Section: Introductionmentioning
confidence: 99%